English Language Improvement through Darsul Idhaf Program - Ni’matul Khoiriyah; Retno Sulfa Turahma; Luri Pringgandani; Xena Artika Hindy; Elia Rustiana (ELITE Association Indonesia, 2023)
This research aim to describe the implementation of listening method in english learning on Darsul Idhaf program and what are obstacles faced by students. Darsul Idhaf is one of method that guide students to improve their academic potency, in this case, especially english language. English learning through listening method conducted by performing contents of english vocabularies both the conversation or song. This process involve students concentration and sensitivity and also the cooperation between students and tutor. This research used qualitative descriptive studies. Data sources in this research are primary and secondary data, data collection procedures used are interview, observation and documentation. The results showed that by this english learning through listening method on Darsul Idhaf program, the tutor gave the well-understanding, guiding and motivating students about english. But there are obstacles in this learning process. The vary of students education background that not all of them have english mastery enough as one of obstacle that faced in this method implementation. Thus, the success of this program depend on the maximum effort, understanding and subject that presented by tutor and students all another policies that implemented continually by the stakeholder and grassroots. Keywords: English Language. Improvement. Darsul Idhaf Program